2008
DOI: 10.1007/s12274-008-8012-9
|View full text |Cite
|
Sign up to set email alerts
|

Wafer scale synthesis of dense aligned arrays of single-walled carbon nanotubes

Abstract: Here we present an easy one-step approach to pattern uniform catalyst lines for the growth of dense, aligned parallel arrays of single-walled carbon nanotubes (SWNTs) on quartz wafers by using photolithography or polydimethylsiloxane (PDMS) stamp microcontact printing (μCP). By directly doping an FeCl 3 /methanol solution into Shipley 1827 photoresist or polyvinylpyrrolidone (PVP), various catalyst lines can be wellpatterned on a wafer scale. In addition, during the chemical vapor deposition (CVD) growth of SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 32 publications
1
65
0
Order By: Relevance
“…What's more interesting is that we are able to obtain aligned SWNTs of very small diameter and with very narrow distribution. In previous reports, the mean diameter of SWNTs grown on quartz with Fe catalysts is usually ranged from 1.2 to 1.7 nm [11,14,25,30]. The diameters of aligned tubes grown on silicon wafers oriented by gas flow are from 0.9 to 3.3 nm with a mean value of 2.0 nm [8].…”
Section: Characterizationmentioning
confidence: 97%
“…What's more interesting is that we are able to obtain aligned SWNTs of very small diameter and with very narrow distribution. In previous reports, the mean diameter of SWNTs grown on quartz with Fe catalysts is usually ranged from 1.2 to 1.7 nm [11,14,25,30]. The diameters of aligned tubes grown on silicon wafers oriented by gas flow are from 0.9 to 3.3 nm with a mean value of 2.0 nm [8].…”
Section: Characterizationmentioning
confidence: 97%
“…In these cases, SWNTs can be grown, in a wafer scale fashion, with linearity to within ~5 nm over lengths of many microns, a n d w i t h d e v i a t i o n s from parallelism of less than 0.1 degree. The D in such "perfectly" aligned a r r a y s i s t y p i c a l l y 2 5 t u b e s / μ m 2 b u t c a n reach peak values of 25 50 tubes/μm 2 in certain areas [22,23]. These types of SWNT configurations a re m o s t s u i t a b l e f o r applications that have demanding performance requirements (e.g., analog radio frequency (RF), where the competition is with compound inorganic semiconductors), where high D, linear confi gurations and a complete absence of SWNT SWNT overlap junctions are paramount.…”
Section: Preparation Of Swnt Thin Fi Lmsmentioning
confidence: 99%
“…The surface resistivity (R x ) of bundled CNT is proportional to the resistance and kinetic inductance of SWNT and is inversely proportional to number density of SWNTs. This one directional current flowing causes the anisotropic property and results in R , the complex surface resistivity dyad as shown in (3). The boundary condition (1) is implemented in a MoM code developed for antenna simulations.…”
Section: Resistive Sheet Model Of Bundled Carbon Nanotubementioning
confidence: 99%
“…In laboratory measurements up to 50 GHz, it was shown that the resistance of bundled CNT is simply equal to component value of discrete circuit element of SWNT divided by its number density [CNTs/µm] [2]. The current fabrication technology produces a number density of 10 [CNTs/µm] in wellaligned arrays [3]. The discrete circuit model of SWNT in theory [4], the series kinetic inductance L k of 16nH/µm and the resistance of 6.5kΩ/µm are employed in this paper.…”
Section: Introductionmentioning
confidence: 99%